PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR POS INDONESIA CABANG PAMULANG PERIODE 2022-2023 - Anisah Syahrani; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of leadership and motivation on employee performance at Indonesian Post Office Branch. The research method used is quantitative. The population in this study was 96 respondents. The results of the analysis show that motivation has a significant effect on employee performance with a significant value of 0.001 < 0.05, and the t count is 17.947 > 1.990 t table. The work discipline has a significant effect on employee performance with a significant value of 0.001 < 0.05, and a calculated t value of 22.772 > 1.990 t table. Motivation and Work Discipline have a significant effect on Employee Performance with the regression equation Y= 0,933 + 0,877X1 + 0,842X2. The coefficient of determination value is 87% while the remaining 13% is influenced by other variables outside this regression equation or variables that are not examined. Hypothesis testing obtained a calculated F value > F table or (311.533 > 3.09).